The THE ROLE OF NITROGEN FERTILISATION IN ENHANCING GROWTH, YIELD, AND SECONDARY METABOLITE PRODUCTION IN MEDICINAL PLANTS: A REVIEW - Olwetu Sindesi; Wandile Mashece; Sibongiseni Silwana; Manelisi Sigidi (Agricultura, 2025)
This review analyses the existing literature on how nitrogen (N) fertilisation impacts the growth, yield, physiology and production of secondary metabolites in medicinal plants, given their increased global demand and concerns over unsustainable harvesting practices. It also highlights the environmental impact of N and further recommends possible practices to reduce the negative environmental impacts of N fertilisation. The methodology involved the review of literature using databases such as Web of Science, Scopus, and Google Scholar. Relevant studies were selected based on their focus on medicinal plants and N fertilisation, and findings were extracted to identify common themes and contradictions. The review highlights that N fertilisation generally enhances plant growth and yield, as demonstrated in various studies involving different medicinal plants and N application rates. However, the response to N fertilisation can vary depending on plant species and environmental conditions.  In terms of physiological responses, increased N availability is typically associated with higher chlorophyll content, improved photosynthesis, and better overall plant health. Nonetheless, excessive N application can lead to reduced secondary metabolite content, which may compromise the medicinal value of the plants. The review also underscores the importance of optimising N fertilisation to balance plant growth and secondary metabolite production, ensuring both economic and therapeutic benefits. In conclusion, while N fertilisation is crucial for the sustainable cultivation of medicinal plants, careful management is needed to avoid negative impacts on secondary metabolite content. Future research should focus on developing tailored N fertilisation strategies for different medicinal plant species to maximise their medicinal and economic potential.